FLOW CHARACTERIZATION FROM A NACA AIR INTAKE ASSEMBLED IN A CANARD TYPE AIRCRAFT - Almeida, O. de; Souza, P. R. C. (Revista de Engenharia Térmica, 2017)
omputational aerodynamics analyses of a NACA air intake assembled in a canard type aircraft is performed in this work. Semi-empirical calculation through the ESDU (Engineering Science Database Unit) preceded the CFD simulations to define the geometric size of the air intake as well to check its efficiency and drag estimation. The NACA air inlet was considered one of the best options available for implementing in a canard type aircraft since it reduces aerodynamic drag by avoiding protuberances in the fuselage. Numerical studies were performed with the air intake mounted in the aircraft’s fuselage at operational flight conditions. These simulations were performed using Reynolds-averaged Navier-Stokes (RANS) and turbulence modeling by using the k-ω SST (Shear-Stress Transport). Data analyses were based on the air inlet efficiency, drag estimation and mainly flow characterization. The numerical results helped to characterize the flow in a canard type aircraft showing that the NACA air intake yielded satisfactory performance with low drag. The approach applied in this work was a partnership with the Brazilian Aircraft Factory (FABE) and Federal University of Uberlândia (UFU) to improve the design of a canard type aircraft. The CFD results have been corroborated by an empirical approach and with some experimental tests performed by the company, pointing towards the reliability of a very efficient design tool for application in industry.